Inhibition of the hemorrhagic activity of Bothrops asper venom by a novel neutralizing mixture - Borkow, Gadi (1997)
This study screened 25 sera, 19 synthetic products and five antivenoms obtained after immunization for their ability to neutralize the hemorrhagic activity of venom from the snake Bothrops asper. Among the sera screened, the homologous serum of B. asper itself was found to possess the highest neutralizing capacity, abolishing the hemorrhagic effect of the venom at weight ratio of 3:1. It was more efficient than the antisera obtained by immunization. Among the synthetic compounds tested, only O-phenanthroline and EDTA salts inhibited the hemorrhagic activity at concentrations of 0.5-10 mM; however, only CaNa2EDTA was non-toxic at the concentrations studied. Intravenous injections and in situ administration of the non-toxic inhibitors revealed that a fraction of B. asper serum, the horse polyvalent antivenom and CaNa2EDTA were the most potent antihemorrhagic materials against B. asper venom, especially when administered in situ as a mixture. This work suggests that this neutralizing mixture could be highly useful in the neutralization of local and systemic hemorrhage developing after B. asper envenomation.